New species and revisions of Pediciidae (Diptera) from the Middle Jurassic of northeastern China and Russia - Gao, Jiaqi; Shih, Chungkun; Kopeć, Katarzyna; Krzemiński, Wiesław; Ren, Dong (Zootaxa, 2015)
Two new species of Praearchitipula Kalugina, 1985, P. apprima sp. nov. and P. mirabilis sp. nov., are described and illustrated from the late Middle Jurassic Jiulongshan Formation of Daohugou in eastern Inner Mongolia, China. In addition, we propose to transfer Architipula abnormis Hao & Ren, 2009 (which is from the same locality of Daohugou) from Architipula of Limoniidae to Praearchitipula of Pediciidae: Praearchitipula abnormis (Hao & Ren, 2009) comb. nov. In addition, we propose to transfer Praearchitipula spasskia Kalugina, 1985 to the genus Mesotipula (Limoniidae, Architipulinae). We also suggest treating Praearchitipula lata Kalugina, 1985 as a junior synonym of Praearchitipula notabilis Kalugina, 1985. An emended generic diagnosis of Praearchitipula is provided.